WASTE APPLICATION OF SEAWEED (EUCHEUMA COTTONII) ON PLANT GROWTH AND RESULTS OF MUSTARD (BRASSICA JUNCEA L.) - suriyani suriyani; Ramal Yusuf; Abd Syakur (Tadulako University, 2017)
Seeing the importance of consuming vegetables and increasing of public demand each day, to increase the maximum production using the fertilizer is one of the solutions, either organic fertilizers or inorganic fertilizers. The objective of this study is to determine the effect of seaweed Eucheuma cottonii waste application on growth and yield of mustard. This study was conducted on January and February 2016. Located in Sidondo, district torch and Seed Technology Laboratory Sciences, Tadulako University, Palu, Central Sulawesi. This study was conducted using a randomized block design (RBD), with treatment consisting of R0 (control), R1 (20% of waste seaweed), R2 (40% of waste seaweed), R3 (60% of waste seaweed), R4 (80% of waste seaweed) and R5 (100% of waste seaweed). Each treatment was repeated four times so that there are 24 experimental units. The results showed that the treatment of waste RO seaweed significantly affect the growth and yield of mustard. R5 (100% of waste seaweed) generating plant height, leaf number, fresh weight, dry weight, better than other treatments.